Plasma Molecular Signatures in Hypertensive Patients With Renin–Angiotensin System Suppression: New Predictors of Renal Damage and De Novo Albuminuria Indicators. Issue 1 (July 2016) - Baldan-Martin, Montserrat; Mourino-Alvarez, Laura; Gonzalez-Calero, Laura; Moreno-Luna, Rafael; Sastre-Oliva, Tamara; Ruiz-Hurtado, Gema; Segura, Julian; Lopez, Juan Antonio; Vazquez, Jesus; Vivanco, Fernando; Alvarez-Llamas, Gloria; Ruilope, Luis M.; et al.
Abstract : Albuminuria is a risk factor strongly associated with cardiovascular disease, the first cause of death in the general population. It is well established that renin–angiotensin system suppressors prevent the development of new-onset albuminuria in naïf hypertensive patients and diminish its excretion, but we cannot forget the percentage of hypertensive patients who develop de novo albuminuria. Here, we applied multiple proteomic strategy with the purpose to elucidate specific molecular pathways involved in the pathogenesis and provide predictors and chronic organ damage indicators. Briefly, 1143 patients were followed up for a minimum period of 3 years. One hundred and twenty-nine hypertensive patients chronically renin–angiotensin system suppressed were recruited, classified in 3 different groups depending on their albuminuria levels (normoalbuminuria, de novo albuminuria, and sustained albuminuria), and investigated by multiple proteomic strategies. Our strategy allowed us to perform one of the deepest plasma proteomic analysis to date, which has shown 2 proteomic signatures: (1) with predictive value of de novo albuminuria and (2) sustained albuminuria indicator proteins. These proteins are involved in inflammation, immune as well as in the proteasome activation occurring in situations of endoplasmic reticulum stress. Furthermore, these results open the possibility of a future strategy based on anti-immune therapy to treat hypertension which could help to prevent the development of albuminuria and, hence, the progression of kidney damage. Abstract : Supplemental Digital Content is available in the text.